Pilots' eye movement patterns during performing air-to-air mission - Li, Wen-Chin; Yu, Chung-San; Li, Lon-Wen; Greaves, Matthew (EAAP, 2014)
Eye movement patterns are linked closely with the cognitive process of encoding information that pilots seek and perceive in the cockpit. A total of 30 qualified mission-ready military pilots participated in this research. The ages of participants are between 26 and 51 years old (M=29, SD=6); and total flying hours between 310 and 2920 hours (M=844, SD=720). Eye movement data were collected by a head-mounted ASL (Applied Science Laboratory) Mobile Eye combined with a jet fighter simulator which is a dynamic high fidelity trainer that replicates actual aircraft performance, navigation and weapon systems. The scenario was an air-to-air (AA) task. To complete the task, pilots have to search for the target with eye contact, pursue for aiming at the target, and lock-on for pick-off. The results showed there were significant differences in pilots’ fixations among the five different areas of interest (AOIs), p<.001. Also, there were significant differences in pupil size (p<.001) for three different operating phases between experienced and less-experienced pilots; however, the average saccade velocity showed no difference. Understanding the pilot’s visual scan pattern for attention distribution whilst pursuing a dynamic target will facilitate aviation professionals in developing an effective training syllabus to improve safety of flight operation.
Keywords: Attention distribution; Eye movement; Cognitive processes; Fixation; Saccade velocity